Perancangan User Interface Sistem Informasi PT. Mulia Perkasa Kontraktor menggunakan Metode Human-Centered Design - Zahrah Putri Ramadhanti; Hanifah Muslimah Az-Zahra; Welly Purnomo (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2022)
PT. Mulia Perkasa Kontraktor (MPK) is a service company whose head office is located in Cirebon City, West Java. The services provided include Cleaning Service, Landscaping, Security, and other services related to property management and maintenance. Based on the results of the study, there were problems found that were related to the processing of PT. MPK. Some staff complained that it was less effective because they had to access several separate applications where the data was stored, some even still doing it manually, namely writing on paper documents. To overcome this, a solution that can help is needed is to design a user interface for data processing information systems PT. MPK which focuses on 4 divisions, namely HRD, operations, logistics, and finance. The design process will use the Human-Centered Design (HCD) method which aims to be a user-focused approach in design. There is a task scenario assessment process using the Single Ease Question (SEQ) and a usability evaluation process using the System Usability Scale (SUS). The average score obtained using SEQ from the four divisions is 6.3, and the average score for the SUS assessment is 81.6.